Arab national security and confrontation strategies (a study in the light of dangers and threats( (قضايا سياسية, 2023)
Arab national security is facing at the current stage many challenges, risks and threats that lie in basic factors. All these factors lead us to diagnose the situation through studying and analyzing it in order to determine the treatment in drawing up and developing a comprehensive strategy to deal with potential and existing risks, in a way that guarantees the continuity of the nation and its existence in this. The crashing sea of dangers that threatens the Arab countries, and then the entire Arab nation, civilization, people and states. Hence, the study was divided into four main axes, as the first axis dealt with: Arab national security (concept, determinants, and dimensions). The second axis deals with the stages of development of the concept of Arab national security. While the third axis deals with: dangers and threats to Arab national security, and finally the fourth axis: confrontation strategies, and a conclusion.